Diversity of Flower Visiting Beetles at Higher Elevations on the Yulong Snow Mountain (Yunnan, China) - Kai-Qin Li (MDPI AG, 2021)
Background: Flowers are one of the important microhabitats promoting beetle diversity, but little is known about variation in the diversity of these insects at higher elevations. We do not know how divergent habitats influence the distribution of beetles among montane flora. Methods: We sampled beetles systematically in angiosperm flowers at 12 sites at two elevations (2700 m and 3200 m) and in two habitats (meadows and forests) for two consecutive years (2018 and 2019) on the Yulong Snow Mountain in Yunnan, southwestern China. Beetle diversity among sites were compared. Their interactions with flowers of identified plant species were analyzed using bipartite networks approach. Results: We collected 153 species of beetles from 90 plant species recording 3391 interactions. While plant species richness was lower at the higher, 3200 m elevation regardless of habitat type, beetle species richness was not significantly different among sites. Plant-beetle interaction networks were strongly modular and specialized. The structure of networks showed greater differences between elevations than between habitats. The turnover of networks was determined by species composition showing a weak influence by interaction rewiring. Conclusion: Our study showed a high diversity of beetles in flowers at higher elevations within this mountain complex. The role of beetles in plant–insect interactions within some sections of temperate, montane sites appear to be underestimated and warrant further study.